The Analysis of Implementation of Re-Purchase Intention Using E-Commerce toward Perceived Benefit, Perceived Risk, Quality System and Satisfaction - Zelika, Liza Ghinaa (Jurnal Ilmiah Mahasiswa FEB, 2016)
E-commerce was a trade transaction contract between buyer and seller using internet media. Shopping with e-commerce delivered many advantages, and one of them was that consumers could buy items through easier selection at shorter time. Online shop was also obtaining profit and income from online sale at cheaper cost to manage. Therefore, research was aimed to examine factors influencing online purchase intention by customers who used e-commerce. Research was done at Faculty of Economic and Business, University of Brawijaya. Method of research was survey. Independent variables were perceived benefit, perceived risk, system quality,  and  shopping  satisfaction.  Repurchase  intention  to  use  e-commerce  in  online shopping was dependent variable. For hypothesis testing, this research applied Partial Least Square (PLS) with sample of 273 persons. Result of analysis in this model showed that perceived benefit, system quality and shopping satisfaction were influential supported to repurchase intention of the customers who used e-commerce in online shopping. Perceived risk was not supported influencing repurchase intention of the customers who used e- commerce in online shopping. Therefore, perceived benefit, system quality and shopping satisfaction were quite influential to repurchase intention of the customers who used e- commerce in online shopping. The implication of research was that the result of research could provide inputs to the management and system developer which enforced them to be more attentive to the variables of shopping satisfaction, perceived benefit, and system quality when they developed and implemented e-commerce transaction.Keywords:    Perceived Benefit, Perceived Risk, Quality System, Satisfaction, Repurchase  Intention, and E-commerce